Cellular and molecular evidence for a role of tumor necrosis factor alpha in the ovulatory mechanism of trout - Bobe Julien; Goetz Frederick W; Krasnov Aleksei; MacKenzie Simon A; Roher Nerea; Bonnet Emilie; Crespo Diego; Planas Josep V (BMC, 2010)
Abstract Background The relevance of immune-endocrine interactions to the regulation of ovarian function in teleosts is virtually unexplored. As part of the innate immune response during infection, a number of cytokines such as tumor necrosis factor alpha (TNF alpha) and other immune factors, are produced and act on the reproductive system. However, TNF alpha is also an important physiological player in the ovulatory process in mammals. In the present study, we have examined for the first time the effects of TNF alpha in vitro in preovulatory ovarian follicles of a teleost fish, the brown trout (Salmo trutta). Methods To determine the in vivo regulation of TNF alpha expression in the ovary, preovulatory brook trout (Salvelinus fontinalis) were injected intraperitoneally with either saline or bacterial lipopolysaccharide (LPS). In control and recombinant trout TNF alpha (rtTNF alpha)-treated brown trout granulosa cells, we examined the percentage of apoptosis by flow cytometry analysis and cell viability by propidium iodide (PI) staining. Furthermore, we determined the in vitro effects of rtTNF alpha on follicle contraction and testosterone production in preovulatory brown trout ovarian follicles. In addition, we analyzed the gene expression profiles of control and rtTNF alpha-treated ovarian tissue by microarray and real-time PCR (qPCR) analyses. Results LPS administration in vivo causes a significant induction of the ovarian expression of TNF alpha. Treatment with rtTNF alpha induces granulosa cell apoptosis, decreases granulosa cell viability and stimulates the expression of genes known to be involved in the normal ovulatory process in trout. In addition, rtTNF alpha causes a significant increase in follicle contraction and testosterone production. Also, using a salmonid-specific microarray platform (SFA2.0 immunochip) we observed that rtTNF alpha induces the expression of genes known to be involved in inflammation, proteolysis and tissue remodeling. Furthermore, the expression of kallikrein, TOP-2, serine protease 23 and ADAM 22, genes that have been postulated to be involved in proteolytic and tissue remodeling processes during ovulation in trout, increases in follicles incubated in the presence of rtTNF alpha. Conclusions In view of these results, we propose that TNF alpha could have an important role in the biomechanics of follicle weakening, ovarian rupture and oocyte expulsion during ovulation in trout, primarily through its stimulation of follicular cell apoptosis and the expression of genes involved in follicle wall proteolysis and contraction.